The Influence of Company Growth, Capital Structure, Company Size, Profitability and Liquidity on Company Value - Rohmah, Aulia Nur; Rahmawati, Ika Yustina; Tubastuvi, Naelati; Alfalisyado, Alfalisyado (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to examine the relationship between Company Growth, Capital Structure, Company Size, Profitability and Liquidity on Company Value in the 2019 - 2022 period. The population used was cyclical companies and sampling used a purposive sampling technique with a total of 27 companies. The statistical analysis techniques used are Descriptive Test, Classic Assumption Test and Multiple Linear Regression Test which uses the t test to test the hypothesis. The method of collecting data was by determining the population used and obtaining 104 data from 26 cyclical companies that had positive profits in their financial reports. From the results of the tests that have been carried out, the growth and capital structure variables have a positive and significant effect on company value. Meanwhile, the variables company size, profitability and liquidity have no significant effect on company value.